Ectopic Pregnancy Reimplanted to Douglas Pouch After Tubal Abortion: A Case Report - Alanbay, İbrahim and Ceyhan, Temel and Gezginç, Kazım and Karaşahin, Emre and Keskin, Uğur and Ergün, Ali and Başer, İskender (Gynecology Obstetrics & Reproductive Medicine, 2008)
A 26 year old Gravida1 Para 0 patient has admitted to our outpatient clinic with the complaints of missed menstrual period, inguinal pain and vaginal spotting for two days. The patient who had an endometrial thickness of 15 mm in her transvaginal ultrasound had no other pathological findings except for a minimal tenderness in deep abdominal palpation. Her β-hCG was reported as 556 IU/ml, therefore she was scheduled for serial β-hCG follow up. Since the follow up revealed first falling and then increasing levels of β-hCG, the possibility of a tubal abortion followed by reimplantation came into discussion. A diagnostic laparoscopy was planned. During laparoscopy, an ectopic pregnancy mass of 2–3 cm was seen to be implanted on the pouch of Douglas. Minimal bleeding was observed from the fimbrial end of the left tuba uterina. Ectopic pregnancy focus was extirpated by a laparoscopic forceps. Pathological examination supported the initial diagnosis of ectopic pregnancy. The patient was followed until the postoperative 6 th week, when the β-hCG level was reported to be <5 IU/ml. We wanted to present this case of ectopic pregnancy implanted to Douglas pouch after the tubal abortion, which we haven’t encountered in the literature previously.